Importance Socioculturelle Des Produits Forestiers Non Ligneux Du Massif Forestier D’agoua Au Benin - Alex, Wotto; Ulrich, Gbaguidi Aholidji Humbert; Sylvain, Vissoh Ahotondji (European Scientific Journal, ESJ, 2017)
The aim of this research is to analyze the socio-cultural importance of non-ligneous forest products (NWFPs) in the forest of Agoua, located in the department of Hills in Benin. This research led to an inventory of NWFPs and ethnobotanical surveys among 50 foresters, 62 NWFP resellers, 46 consumers and 12 phytotherapists. The data collected relate to the plant species used as NWFPs by populations living on the massif of Agoua, to endogenous knowledge and to the use values of NWFPs. Thus, 105 plant species distributed in 48 families have been inventoried within the forest massif of Agoua. The determination of the different categories of NWFP uses revealed that 61 (58.09%) of the total number of plant species surveyed were used in traditional medicine, 30 in food (28.57%), 28 for various domestic uses (26.57%), 8 for building materials (7.61%), 6 for packaging (5.71%) and 4 for coloring (3.8%). The organs taken by the populations vary from one species to another and according to the use they make of them. In fact, it is the leaves, fruits, barks, flowers and roots that are used by the populations bordering the forest of Agoua. The excessive exploitation of NWFPs by the populations bordering on the Agoua forest is the cause of the decline and disappearance of these plant species with a high genetic and socio-cultural potential. The aggravation of this phenomenon with population growth may be detrimental to the sustainability of this forest ecosystem. In order to reduce the effects of such use, it is necessary to implement methods and collection rates that respect the sustainability of these resources.